LEVEL OF COMPLIANCE WITH THE USE OF ANTI-TUBERCULOSIS DRUGS IN ADULT PULMONARY TUBERCULOSIS PATIENTS AT THE OUTPATIENT PULMONARY POLYCLINIC OF DR. HARJONO S PONOROGO - Nasruhan Arifianto; Susilowati Andari; Riza Mazidu; Nabila Sri Andhini (Jurusan Farmasi, Poltekkes Kemenkes Palembang, 2025)
Background: Tuberculosis is an infectious disease that causes health disorders and is the leading cause of death worldwide. Adherence to medication is a very important indicator of the successful recovery of tuberculosis patients for 6-9 months where patients have to take medication non-stop. Non-compliance of TB patients causes low patient recovery, high mortality rate, increased recurrence, and more fatal is the occurrence of (immunity) of germ resistance to standard treatment. This study has a formulation of the problem of how the level of compliance with the use of anti-tuberculosis drugs in adult pulmonary TB patients at Dr. Harjono Ponorogo Hospital. Methods: This research is a qualitative descriptive research with a survey method. The instrument used to collect data by providing a closed statement on a questionnaire sheet that has been tested for valdiance and reliability. The research was conducted at the Outpatient Pulmonary Poly of the Dr. Harjono Ponorogo Regional General Hospital in April 2024. The sample in this study was taken from patients who were undergoing advanced phase pulmonary TB treatment at least 4 months after treatment, were over 17 years old, and were willing to be respondents. The sample amounted to 22 respondents with a sampling technique using the purposive sampling technique. The data obtained were analyzed using univariate analysis., Results: Result of the study showed that good compliance amounted to 16 patients (72.7%), moderate compliance amounted to 5 patients (22.7%) and less than 1 patient (4.5%). Conclusion: It was concluded that the compliance rate for the use of anti-tuberculosis drugs at Dr. Harjono Ponorogo Hospital had good compliance of 72.7%.